Coverage of Socioeconomic and Political Issues Related to Muslims in Kannada and Urdu Dailies - Sultana, Tahmeena Nigar (Journal of Advanced Research in Journalism & Mass Communication, 2018)
This study investigates the coverage of socioeconomic and political issues related to Muslims in Karnataka. For the study, Kannada newspaper Prajavani and Urdu newspaper Sahara for the period of two months, i.e., January and February 2017 were selected. A total of 60 newspapers in total were chosen to analyze the prioritized coverage of issues in newspapers to examine how the socioeconomic and political issues related to Muslims were covered in daily Kannada and Urdu newspapers. This study also compared the coverage of socioeconomic and political issues related to Muslims in Kannada and Urdu newspapers. The methodology adopted was quantitative content analysis. Major categories such as news stories, articles, advertisements, editorials, etc., were evaluated. How to cite this article: Sultana TN. Coverage of Socioeconomic and Political Issues Related to Muslims in Kannada and Urdu Dailies. J Adv Res Jour Mass Comm 2018; 5(3): 8-13. DOI: https://doi.org/10.24321/2395.3810.201808